Faqrur receives UMPSA 2024 Mercu Sanjung Award, elevates dignity of arts and cultural heritage - Naqiah, Puaad (UMPSA, 2025)
GAMBANG, 16 April 2025 – The name of Nurhaiqal Faqrur Islam Norashid is now proudly etched in the history of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) as he was announced the recipient of the UMPSA 2024 Mercu Sanjung Award during the recent glittering 2024 Mercu Sanjung Awards Night (MARS) held at the UMPSA Sports Complex Hall.